1992
DOI: 10.5144/0256-4947.1992.352
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Choledochoduodenostomy (ECDT): A Practical Approach to Management of Impacted Papillary Gallstones and Ampullary Tumors

Abstract: We report five cases of impacted papillary stones and two cases of ampullary carcinoma treated by endoscopic choledochoduodenostomy (ECDT) at Riyadh Armed Forces Hospital (RAFH).The procedure was carried out successfully in all five cases with impacted stones and in one of the two cases of ampullary carcinoma. No complications were noted. In the presence of the necessary endoscopic expertise and in cases of impossible cannulation of the papilla of Vater due to stone impaction or the presence of a papillary tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Papillotomy is standard treatment for gallstone impaction 1 2 3 4 5 6. Dramatic improvements can be expected from the removal of stone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papillotomy is standard treatment for gallstone impaction 1 2 3 4 5 6. Dramatic improvements can be expected from the removal of stone.…”
Section: Discussionmentioning
confidence: 99%
“…Gallstone impaction at the ampulla of Vater can cause cholangitis as well as pancreatitis, and urgent stone removal is critical for improving the patient’s condition 1 2 3 4 5 6. Occasionally, the clinical course is fatal.…”
Section: Introductionmentioning
confidence: 99%
“…4 The risk of post papillotomy bleeding and perforation is increased with the use of needle knife papillotomy; therefore, it is recommended that this be performed by an experienced endoscopist. Needle knife precut papillotomy provides access into the biliary system and facilitate subsequent deep cannulation and completion of the papillotomy using a standard papillotome.…”
Section: Discussionmentioning
confidence: 99%
“…Suppurative cholangitis is associated with a significantly high morbidity and mortality and warrants urgent ERCP for biliary decompression and removal of the impacted stone. [1][2][3][4] However, stone impaction often leads to swelling and deformity of the papilla and the impacted stone makes deep cannulation and standard papillotomy technically difficult. Needle-knife precut papillotomy has been described for the removal of an impacted ampullary stone but this is risky especially when performed by inexperienced or trainee endoscopists.…”
Section: Introductionmentioning
confidence: 99%
“…In such conditions, a needle-knife has been used to gain access to the biliary tree for both diagnostic and therapeutic purposes [2][3][4][5][6]. AlKarawi et al [7] recently reported the successful use of needle-knife in performing endoscopic choledochoduodenostomy in five such cases of distal ampullary obstruction. We would like to share our experience in similar circumstances.…”
mentioning
confidence: 99%